(−)-Tetrahydroberberrubine∙acetate accelerates antioxidant potential and inhibits food associated Bacillus cereus in rice. (1st March 2021) - Bajpai, Vivek K.; Park, InWha; Khan, Imran; Alshammari, Fanar Hamad; Kumar, Pradeep; Chen, Lei; Na, MinKyun; Huh, Yun Suk; Han, Young-Kyu; Shukla, Shruti
Highlights: Characterization of a protoberberine alkaloid (−)-Tetrahydroberberrubine∙acetate. Potentiation of cellular antioxidant activity by (−)-Tetrahydroberberrubine∙acetate. Biofilm inhibition by (−)-Tetrahydroberberrubine∙acetate on glass substrate. (−)-Tetrahydroberberrubine∙acetate compromising membrane permeability parameters. Inhibition of B. cereus in a rice food model by (−)-Tetrahydroberberrubine∙acetate. Abstract: A protoberberine alkaloid, (−)-tetrahydroberberrubine∙acetate (THBA) was assessed for its antioxidant potential and ability to inhibit the growth of a food hazard bacterium Bacillus cereus in vitro and in situ . THBA displayed significant and dose-dependent cellular antioxidant potential against hydrogen peroxide-induced oxidative stress in NIH 3T3 fibroblast cells and decreased the ROS levels as well as increased the expression levels of SOD1 and SOD2 enzymes. The inhibitory spectrum of THBA confirmed its mechanistic role in the disruption of the membrane integrity of B. cereus as evidenced by the results of time-inactivation, cell membrane integrity, NPN membrane uptake, membrane potential, and electron microscopy analyses. Moreover, THBA inhibited biofilm formation by B. cereus and disrupted pre-established biofilms on a glass surface. Furthermore, THBA was also able to inhibit B. cereus in raw rice with a significant amount of reduction in CFU counts, suggesting its potential role as a natural antioxidant and antimicrobial agent.